Synthesis of Ribose-Coated Copper-Based Metal-Organic Framework for Enhanced Antibacterial Potential of Chloramphenicol against Multi-Drug Resistant Bacteria - Haseena; Adnan Khan; Iqra Ghaffar; Roua S. Baty; Mohamed M. Abdel-Daim; Shahida M. Habib; Tasmina Kanwal; Muhammad Raza Shah (MDPI AG, 2021)
The rise in bacterial resistance to currently used antibiotics is the main focus of medical researchers. Bacterial multidrug resistance (MDR) is a major threat to humans, as it is linked to greater rates of chronic disease and mortality. Hence, there is an urgent need for developing effective strategies to overcome the bacterial MDR. Metal-organic frameworks (MOFs) are a new class of porous crystalline materials made up of metal ions and organic ligands that can vary their pore size and structure to better encapsulate drug candidates. This study reports the synthesis of ribose-coated Cu-MOFs for enhanced bactericidal activity of chloramphenicol (CHL) against Escherichia coli (resistant and sensitive) and MDR Pseudomonas aeruginosa. The synthesized Cu-MOFs were characterized with DLS, FT-IR, powder X-ray diffraction, scanning electron microscope, and atomic force microscope. They were further investigated for their efficacy against selected bacterial strains. The synthesized ribose-coated Cu-MOFs were observed as spherical shape structure with the particle size of 562.84 ± 13.42 nm. CHL caused the increased inhibition of E. coli and MDR P. aeruginosa with significantly reduced MIC and MBIC values after being encapsulated in ribose-coated Cu-MOFs. The morphological analysis of the bacterial strains treated with ribose-coated CHL-Cu-MOFs showed the complete morphological distortion of both E. coli and MDR P. aeruginosa. Based on the results of the study, it can be suggested that ribose-coated Cu-MOFs may be an effective alternate candidate to overcome the MDR and provide new perspective for the treatment of MDR bacterial infections.